PENGEMBANGAN INSTRUMEN PENGUKURAN HASIL PEMBELAJARAN MATA KULIAH PRONUNCIATION - -, Jamilah; Purnawan, Ari (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2010)
The study aims at developing a valid and reliable test to measure students' Englishpronunciation mastery. To meet the objective, two kinds of instruments were developed,namely recognition and production tests. The instruments were tried out to students fromthree pronunciation classes, and the results were then analyzed through validity andreliability tests and an item analysis. Statistical analyses showed that the instruments wereunsatisfactory and needed revisions. After some revisions and try-outs, the revisedinstruments proved to be valid and reliable with reliability coefficients of 0.940 for theproduction test and 0.889 for the recognition test, and difficulty indices of 0.538(moderate) and 0.546 (moderate) respectively.Keywords: pronunciation, validity, reliability, difficulty indices